New technique for femtosecond laser creation of clear corneal incisions for cataract surgery. Issue 3 (January 2017) - Serrao, Sebastiano; Giannini, Daniela; Schiano‐Lomoriello, Domenico; Lombardo, Giuseppe; Lombardo, Marco
Abstract : Purpose : To evaluate the changes in corneal topography and corneal higher‐order wavefront aberrations with the use of a new technique in which clear corneal incisions (CCIs) for cataract surgery are created with a femtosecond laser. Setting : IRCCS Fondazione G.B. Bietti, Rome, Italy. Design : Prospective randomized case series. Methods : Cataract surgery patients were randomized into 2 groups. In the study group, a 3‐plane CCI was created with a femtosecond laser. In the control group, the single plane‐angled CCI was created manually using disposable knives. Simulated keratometry (K) values and corneal higher‐order wavefront aberrations with 3.5 mm and 6.0 mm pupils were compared between groups. Results : Each group comprised 10 eyes. At 6 months, the mean change in K values from preoperatively was 0.16 diopter (D) ± 0.14 (SD) in the study group and 0.34 ± 0.16 D in the control group, with no differences between groups ( P > .05). The manual CCI significantly increased corneal higher‐order wavefront aberrations with 3.5 mm and 6.0 mm pupils (both P < .05). In the study group, corneal higher‐order wavefront aberrations increased significantly with a 6.0 mm pupil only ( P ≤ .02). The induced changes in corneal higher‐order wavefront aberrations were significantly different between groups over both pupil sizes ( P < .05). Conclusions : The femtosecond laser–created CCI did not induce significant changes in simulated K or corneal higher‐order wavefront aberrations over the mesopic pupil size. The lower amount of induced corneal higher‐order wavefront aberrations with the new technique than with manual CCI could be related to the different geometry of the 2 techniques.